Prolonged repellent activity of Ruta graveolens essential oil adsorbed on different mineral matrices against Sitophilus zeamais (L.) (Coleoptera: Curculionidae). (May 2022) - Perera, A.G.W.U.; Karunaratne, M.M.S.C.; Chinthaka, S.D.M.
Abstract: Plant-derived essential oils (EOs) have been considered as promising alternatives to conventional insecticides. But because of their high biodegradability and rapid volatilization, EOs are not persistent. To overcome this drawback of short protection time, EOs can be adsorbed onto protective mineral matrices to enhance efficiency by slowing down volatilization. This work was aimed at assessing the potential effectiveness of Ruta graveolens L. (Rutaceae) essential oil (RGEO)-adsorbed zeolite (ZEO) and cloisite 20A (C20A) mineral bio-composites in prolonging the odor-driven repellent efficacy of RGEO towards Sitophilus zeamais (L.) (Coleoptera: Curculionidae). Chemical profile of RGEO was identified using GC and GC-MS. Produced bio-composites were physiochemically characterized by FTIR, SEM-EDS, and TGA. The compounds, 2-undecanone (44.7%) and 2-nonanone (30.3%) were the major constituents of RGEO. Repellent action of bio-composites accounting for 50–100% was persisted for 90 d towards S. zeamais adults, whereas the RGEO used without the adsorbents recorded 0% and 44% of repellent potency within 24 h at the lowest and highest concentrations respectively. Given the volatility of RGEO, IR analyses demonstrated successful adsorption and 90-d long persistence of RGEO on both mineral matrices. Micro-/nanostructural architecture of bio-composites ranged from hierarchically porous for ZEO to intercalated platelets for C20A. EDS imaging confirmed the homogenous dispersion of constituent elements of RGEO on both mineral matrices. Bio-composites indicated improved thermal stability in the presence of air flow relative to the neat mineral matrices. Repellent potency of the bio-composites was arranged in the sequence, RGEO-ZEO < RGEO-C20A throughout the 90 d of experimental period. Findings further suggested that formulations based on EOs adsorbed on solid minerals represent a promising strategy in overcoming EOs' limitations through retaining enough volatility while maintaining their slow release, thereby prolonging the repulsive effect of EOs for use in stored-product protection. Highlights: 2-Undecanone and 2-nonanone were major constituents of R. graveolens essential oil. Composed slow release hybrids adsorbing R. graveolens essential oil (EO) on mineral. Adsorptive power and stability of EO on cloisite 20A was greater than on zeolite. EO/mineral hybrids showed extended release and repellency for 90 d on S. zeamais . Negative chemotropism on insects was provoked by EO/cloisite 20A than EO/zeolite.